Seismic Risk Assessment of Ancient Timber Structures Based on Improved Matter-element Extension Model - Chenzi ZHAI; Xiaodong GUO; Wei WANG (Taiyuan Ligong Daxue xuebao, 2023)
In order to accurately predict the risk level of ancient timber structures under earthquake,22 evaluation indexes were selected, including hazard of disaster-causing factors, susceptibility assessment of disaster environment, and vulnerability of disaster-bearing body, combined with seismic damage characteristics and structural characteristics of ancient timber structures, and an earthquake risk assessment model was established by using the improved matter-element extension model. In this model, closeness degree is used instead of correlation degree, which improves the accuracy of evaluation results. This model was used to evaluate the risk of an ancient timber structure under different ground motion levels. The results show that the ancient timber structure is at moderate risk when the peak acceleration of ground motion is 0.05g, 0.10g, and 0.20g, and when it encounters earthquakes with peak ground accelerations of 0.40g, it becomes at a higher risk.